“Comparativo de fuentes y dosis de potasio sobre el rendimiento del cultivo de arroz bajo riego con la variedad capirona (oryza sativa) en suelos de catachi – San Martín” - Córdova Vela, Kelvin (2005)
In arder to evaluate the effect of two sources and tour dose of potassium comparatively on the yield in the cultivation of rice to the transplante and to determine the relationship 1 benefit cost of the two sources and dose of potassium in the diversa treatments; he/she was carried out the present experiment in the 1 am founded of the National University of San Martin-Tarapoto, located in the District of Cacatachi, County and Region San Martin, to 12 Km of the North Highway Femando Belaunde T erry, left margin; likewise the Design of Blocks was used Randomizado Completely (DBCR) with factorial arrangement of 2 x 4 with 4 repéti'tions far treatment. The ~. components in study were: 2 sources of potassium (Chloride of potassium and sulfate of potassium) with 4 fertilization dose (O; 60; 120 and 240 Kg/ha of K20) The results demonstrated that in and 1 is founded, the potassium is not still a restrictive factor for the yield in spite of the years in production. However it should not be neglected the fertilization like a maintenance factor to the floor; likewise it was not observed significant differences among used sources of potassium; but a tendency exists to improve the yields .in kilos for hectare of rice in shell with sulfate of potassium; likewise a bigger resistance to the damage caused by Pyricularia orizae. With the application of sulfate of potassium a tendency was noticed to improve sorne physiologic aspects, since it .is obtained a bigger height, smaller quantity of grains vain, bigger weight of 1000 grains and yields but you standardize. The biggest net profit was obtained with O Kg/ha of chloride and sulfate of potassium, with utilities of S l. 3 700,57 and 3 421,27 new suns and a relationship benefit cost of, 2,08 and 2,00 respectively.